KEHIDUPAN SOSIAL EKONOMI SINGLE MOTHER DALAM RANAH DOMESTIK DAN PUBLIK - Afina Septi Rahayu (Jurnal Analisa Sosiologi, 2017)
Self-sufficiency in the soul of a single mother is needed to run a dual role in the domestic sector, that is to serve in household affairs such as cooking, washing dishes and clothes, cleaning the house, preparing food for the family, taking care of, raising and educating her children and in the public sector economic duty so that the needs remain fulfilled is to earn a living for the family and socially that is socializing with the community. The balance of domestic and public roles needs to be accomplished with extra effort through a process of patience, knowledge, and consistency to run it. As a single mother to work for a living, there must be a lot to consider from a relative income source, an efficient time to be able to carry on the main task of being a single mother without putting aside the household chores, therefore as a single mother, women are required to be able to adapt and move on without a husband, earn a living and balance between domestic and public roles. This research aims to determine the implementation of social economic live doing single mother as a single parent in maintaining the survival of his family in Cepokosawit village. This research used descriptive qualitative method to produce and process the research data descriptive nature, such as transcripts of interviews and observations. The population in this study are all citizens of the women in Cepokosawit village, Sawit district, Boyolali regency.The selected Informants were several single mothers in Cepokosawit village. The technique of taking informants using purposive sampling based on certain criteria. The collection of data carried out by interview and observation. The validity of the data using triangulation techniques and triangulation resources. Data analysis technique is done by means of data collection, data reduction, data display and drawing conclusions or data verification. The results of this research are, First, social strategy that is indicated by a single mother is to live with their parents to avoid social pressure on communities, involve their parents in take care of their child when single mother go to work, participate in various activities in the community to eliminate a bad impression of the single mother and be independent in raising and caring for children without the involvement of ex-husband. Second, the economic adaptation strategies in a single mother family visible in how they align with the amount of income a family needs every day of his life and their strategy for living place by staying at their parent’s home. Forms of economic planning is also evident from the way a single mother to save, set aside in part piecemeal revenue that could be used to meet the needs of their child's education and are used for urgent needs.Keywords: Single Mother, Social, Economic, Talcott Parsons, AGIL Concept.AbstrakKemandirian dalam jiwa single mother diperlukan untuk menjalankan dua peran dalam sektor domestik, yaitu untuk menjalankan rumah tangga seperti memask, mencuci piring dan pakaian, membersihkan rumah, menyiapkan makanan untuk keluarga, merawat, membesarkan dan mendidik anak dan di sektor publik tugas ekonomi perlu untuk dipenuhi sehingga dapat mencari nafkah untuk keluarga dan secara sosial yakni bersosialisasi dengan komunitas.Keseimbangan anfara peran domestik dan publik perlu dicapai dengan usaha tambahan melalui proses kesabaran, pengetahuan dan konsistensi untuk menjalankannya. Sebagai single mother untuk berkerja mencari nafkah, terdapat banyak pertimbangan dari sumber penghasilan, efisiensi waktu untuk dapat menjalankan tugas utama sebagai seorang ibu tanpa mengesampingkan pekerjaan rumah tangga, oleh karena itu sebagai single mother, perempuan dituntut untuk dapat beradaptasi dan melanjutkan tanpa suami, mencari nafkah dan menyeimbangkan antara peran domestik dan publik. Tujuan dalam penelitian ini adalah untuk menentukan implementasi kehidupan sosial ekonomi sebagai single mother  sebagai orang tua tunggal dalam mempertahanan keberlangsungan hidup keluarga di Desa Cepokosawit. Penelitian ini adalah penelitian deskriptif kualitatif untuk memproduksi dan memproses data penelitian dengan cara deskriptif naratif, yakni transkrip dari wawancara dan observasi. Populasi dalam penelitian ini adalah semua penduduk perempuan di Desa Cepokoksawit, Kecamatan Sawit, Kabupatan Boyolali. Terdapat beberapa informan single mother yang dipilih di Desa CepokosawitTeknik pengambilan sampel dalam penelitian ini menggunakan purpsive samplingberdasarkan beberapa kriteria. Teknik pengumpulan data dilakukan dengan wawancara dan observasi. Teknik validitas data menggunakan triangulasi teknik dan triangulasi sumber. Teknik analisis data menggunakan teknik pengumpulan data, reduksi data, tampilan data dan menarik kesimpulan atau verifikasi data. Hasil dari penelitian ini adalah, pertama, strategi sosial yang ditunjukan oleh seorang single mother hidup dengan orang tua mereka untuk menghindari tekanan sosial dalam komunitas, melibatkan orang tua mereka dalam merawat anak ketika single mother pergi bekerja, berpartisipasi dalam berbagai macam kegiatan dalam komunitas untuk mengeliminasi pandangan negatif terhadap single mother dan menjadi mandiri dalam membesarkan anak tanpa keterlibatan mantan suami.Kedua, strategi adaptasi ekonomi dalam keluarga single mother  terlihat dalam bagaimana mereka menyelaraskan dengan jumlah pendapatan dan kebutuhan keluarga setiap hari dan strategi mereka untuk tinggal di rumah orang tua mereka. Dari rencana ekonomi juga jelas terlihat dari cara single mother untuk menabung, mensisihkan pendapatan yang dapat digunakan untuk memenuhi kebutuhan pendidikan anak dan digunakan untuk kebutuhan mendadak.Kata Kunci: Single Mother, Sosial, Ekonomi, Talcott Parsons, Konsep AGIL.